2015
DOI: 10.1007/s00586-015-3929-7
|View full text |Cite
|
Sign up to set email alerts
|

Fusion rate following extreme lateral lumbar interbody fusion

Abstract: Reports of XLIF fusion rate in the literature vary from 85 to 93 % at 1-year follow-up. Fusion rate in our series corroborates data from previous publications. The results of this series confirm that anterior inter body fusion by means of XLIF approach is a technique that achieves high fusion rate and satisfactory clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 11 publications
2
75
0
3
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12] However, given the inherent axial and coronal stability of a large anterolateral cage, the structural necessity of invasive/extensive PSF in ALIF/LLIF has come into question, particularly in single-level application. Accordingly, a growing body of literature exploring less invasive and less demanding alternatives for secondary stability in ALIF/LLIF has emerged.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12] However, given the inherent axial and coronal stability of a large anterolateral cage, the structural necessity of invasive/extensive PSF in ALIF/LLIF has come into question, particularly in single-level application. Accordingly, a growing body of literature exploring less invasive and less demanding alternatives for secondary stability in ALIF/LLIF has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39] Rigid interspinous process fixation (ISPF) is one such alternative modality receiving increased consideration as an adjunct to ALIF/LLIF. 1,[18][19][20]23,29,31 Given the favorable proximity of the spinous processes, one can achieve robust sagittal stability while largely preserving the paraspinal muscles, avoiding the posterior neural elements, and conserving the facets. 1,[18][19][20]23,29,31,40 However, despite such biomechanical and perioperative benefits, reports of midterm and long-term clinical outcomes with ISPF are limited and retrospective in design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent series of 125 patients from Rao et al (10) demonstrated an overall fusion rate of 98% for ALIF using a variety of bone graft substitutes (iFactorCerapedics, Westminster, Colorado, Infuse-Medtronic, Memphis, Tennessee, autologous iliac crest bone and allograft). Similarly, Berjano et al (37) also reported a fusion rate of 98% for XLIF in their series of 77 patients using a combination of autologous bone, calcium triphosphate and Attrax (Nuvasive). Rodgers et al (38) reported XLIF a fusion rate of 93.2% with a mean follow-up of 17.3 months utilizing autograft and demineralized bone matrix with bone marrow aspirated from the iliac crest.…”
Section: Fusion Ratesmentioning
confidence: 88%
“…When the decision to proceed with fusion is made, debate again exists about the method to use. MIS techniques attempt to provide a stable fusion construct while minimizing collateral damage that may further progress the underlying disease process (14,15). SA-LLIF is a relatively new technique that attempts to minimize the deleterious effects of posterior instrumentation while still providing a reliable segmental fusion.…”
Section: Discussionmentioning
confidence: 99%